Soliton, Rogue Wave and Double Layer in an Unmagnetized Collisionless Plasma - Hafez, M.G. (Springer Science and Business Media Deutschland GmbH, 2022)
This chapter deals with the ion-acoustic (IA) solitons, rogue waves (RWs), and double layers (DLs) in multi-component plasmas consisting of positively charged ion fluid and (Î±, q) -distributed electrons as well as positrons. The nonlinear evolution equations, namely, Kortewegâde Vries equation (KdVE), modified KdV equation (mKdVE), nonlinear SchrÃ¶dinger equation (NLSE) and standard Gardner equation (SGE) along with their solutions are derived using the reductive perturbation method. It is examined that KdV, and SG solitons, RWs and DLs are supported both of positive and negative electrostatic potential structures, but mKdV supports only negative electrostatic potential structure by depending on the related plasma parameters. The outcomes presented may be very helpful in understanding the behavior of nonlinear coherent structures in many astrophysical and space environments and the future experimental studies in laboratory. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.